Incidence and persistent infection rates of type-specific HPV among HIV-infected males in China: a 5-year retrospective study - Zhang, Siwei; Liu, Huan; Huang, Zhiyan; Duan, Siyu; Zhang, Yuting; Li, Yanjing; Chu, Wenzhu; Wang, Yan; Yang, Rongqing; Wei, Lanlan (Frontiers in Public Health, 2025)
BackgroundAlthough the 9-valent HPV vaccine (9v-HPV) has been approved for males in China, it has received limited public attention. This study aimed to explore the incidence and persistence of different HPV types in HIV-related males and emphasize the importance of vaccination.MethodsA cohort of 758 male patients with multiple HPV detection (≥3) from 2018 to 2023 in our hospital were enrolled for statistical analysis, including 113 Men who have Sex with Men (MSM) patients. HIV and HPV infection statuses were confirmed respectively by ELISA, PCR, WB and nucleic acid kit.ResultsStatistical analysis revealed that the incidence of 9v-HPV-covered high-risk (HR) HPV infections were 68.1% (HIV+ total males), 43.2% (HIV− total males), 67.6% (HIV+ MSM) and 42.2% (HIV− MSM). HPV persistence was significantly prolonged in HIV+ patients than HIV− cases (p < 0.001). Markov model demonstrated that HIV increased incidence risks of HPV52, 58, 45, 35, 39, 51, 59, 68, 66, 73, 82, 81 and reduced the clearance rates of HPV16, 18, 6, 11, 58, 33, 31, 56 in males.DiscussionThese findings highlight the increased burden of HPV infection among HIV+ individuals. Timely vaccination will benefit males by preventing HPV infection and consequently reducing the associated disease burden.